Fish Diversity, Abundance and Gear Usage in the Lower River Benue, Ibi Local Government Area, Taraba State, Nigeria - Igbani, Flourizel; Abhulimen, Ronald Winifred; Samaila, Fwaseh (Darul Yasin Al Sys, 2024)
The Lower River Benue is one of the largest inland ecosystems in Nigeria and has suffered depletion of fisheries resources which attest to the increasing rate of anthropogenic activities. The study therefore eval_uates the fish diversity, composition, abundance and fishing activities in the Lower River Benue. The study was designed to have three (3) sampled stations, the selected stations were: A-Baruwana, B-Gugu-audulahi and C- Basibi. The stations were sampled for fish with the fisherfolk, two times a week for three (3) months, from October to December, 2022. Fish caught were identified with the aid of identification keys. A total catch of 17,400 comprising of 55 fish species belonging to 23 families, 14 orders and 42 genera were recorded, including two (2) amphibians (Chelonoidis niger and Pelophylex kl. esculentus); species family diversity recorded the highest with the family Mormyridae (14.55%) with 8 species, while Dischondontidae, Bagridae, Protopteridae, Malapteruridae, Ariidae, Hepsetidae, Latidae, Osteoglossidae, Channidae, Nephropidae, Tetraodontidae, and Ampullariidae (1.82% each) were recorded the least with 1 species respectively; relative abundance was recorded highest with L. Senegalensis (8.57%), while least in C. zillii and T. lineatus with (0.01%) each. Six (6) traditional fishing gears were identified from the local fisherfolk with their local names (in Hausa): Long Line (Mari-mari), Gura net trap (Mali), Scoop net (Hooma), Cast net (Birgi), Gill net (Raga-bilili) and Hook and line (Kugiya). Catch Per Unit Effort (CPUE) recorded highest kilograms (17.83kg/day) in Station A, while the least kilograms (5.82kg/day) was recorded in Station C. Analysis of variance (ANOVA, P<0.05), showed that there was no significant difference in fish species diversity and relative abundance within groups (stations). It is highly recommended that the anthropogenic activities along the River should be monitored to avoid overfishing of its fishery resource for biodiversity management, conservation, water quality for survival and reproduction towards fish sustainability.